PERLINDUNGAN KONSUMEN TERHADAP BARANG PESANAN YANG TIDAK SESUAI DALAM TRANSAKSI ONLINE MELALUI SHOPEE - Ni Komang Sri Novia Dewi; Ni Made Jaya Senastri; Made Puspasutari Ujianti (Berajah Journal, 2026)
In the practice of trading through the Shopee platform electronic system, there are still frequent discrepancies between the goods received by consumers and those agreed upon, both in terms of quality, quantity, and specifications, thus potentially causing losses and legal uncertainty. This study aims to analyze the validity of electronic buying and selling transactions through Shopee and the form of legal protection for consumers against losses that arise. The method used is normative legal research with a statutory regulatory approach and a conceptual approach. The results of the study indicate that transactions through Shopee are valid legal acts as long as they meet the requirements for a valid agreement according to the Civil Code and are recognized in the provisions of the ITE Law and the PP PMSE. Consumer protection is provided preventively through the obligation to provide correct information and repressively through compensation mechanisms and dispute resolution, although its implementation is not yet optimal and still requires strengthening.